Critical Ligand Binding Sequences of the Esr1 Gene: What Role in the Treatment of Er(+) Breast Cancers? - Mojica, MD, Wilfrido D.; Mojica, Paul; Sykes, PhD, Don (North American Journal of Medicine and Science, 2016)
The malignant cells in a majority of breast cancer patients express the estrogen receptor. This has been exploited in the clinic through the use of anti-estrogens with much success. However, a certain percentage of patients do not respond to this form of treatment. There are several possible reasons for this, but one mechanism not previously investigated is the presence of single nucleotide polymorphisms in the critical amino acids responsible for ligand binding. As a developing paradigm, variations in critical sequences of a gene may translate into altered proteins, eventually leading to therapeutic failure in the clinic. In this study we sought to determine if the frequency of genetic polymorphisms in the amino acids for estrogen receptor alpha that had previously been reported to be critical for ligand binding with hydroxy-tamoxifen warranted examination prior to the administration of this drug. The sequences corresponding to the critical amino acids were found to be wild type in this study’s cohort of treatment naïve breast cancer patients. This finding, the absence of any alterations in the critical amino acids of the estrogen receptor gene responsible for ligand binding, argue against this mechanism having any significant role in the unresponsiveness of some patients to estrogen therapy. [N A J Med Sci. 2016;9(3):88-95. DOI: 10.7156/najms.2016.0903088]